Outlier Resistant Time Series Operations via Qualitative Robustness and Saddle-Point Game Formalizations- A Review: Filtering and Smoothing - Burrell, Dr A. T.; Papantoni-Kazakos, Dr. Titsa (Discoveries in Agriculture and Food Sciences, 2018)
Abstract: Time series operations are sought in numerous applications, while the observations used in such operations are generally contaminated by data outliers. The objective is thus to design outlier resistant or “robust” time series operations whose performance is characterized by stability in the presence versus the absence of data outliers. Such a design is guided by the theory of qualitative robustness and is completed by saddle-point game formalizations. The approach is used for the development of outlier resistant filtering and smoothing operations.